Fenomena Konsep Diri Perempuan Pelaku Kawin Kontrak di Kawasan Puncak Bogor, Jawa Barat - Cellina Stevani; Asep Syaiful Bahri (Jurnal Hospitality dan Pariwisata, 2017)
Many benefits can be felt by the local community with the presence of tourists Middle East, such as the presence of new business opportunities as a business place or a restaurant meal, lodging or hotel, convenience stores, clothing stores and souvenirs, as well as services travel or scouting, transportation services, even haddamah community, the people who have the ability to cook specifically for Middle Eastern cuisine. In addition to tourist activities undertaken by Middle Eastern tourists, sometimes there is also participating in social activities such as donating funds for the construction of mosques or schools. But the benefits are felt by residents around the tourist arrivals in the Middle East in improving its economy is not only related to things - positive things that have been mentioned above. As it is common knowledge that the practice of temporary marriages in the tourist area of Puncak Bogor with local women. The purpose of this research to know the concept of self-possessed women offenders marriage contract in Region travel Puncak, Bogor West Java. Research is conducted methodology used is descriptive qualitative